Treatment of Mucous Retention Cyst in Association with Sinus Lift and Implant Placement: A Case Report with 1-Year Follow-Up - Antoine Berberi; Georges Aad; Sara Kebbe; Rebecca El Hachem; Nabih Nader (Case Reports in Dentistry)
Sinus lift augmentation techniques, lateral or crestal approaches, have been well documented, with bone substitute graft, or without bone material, with immediate or delayed implant placement as a treatment option for the atrophic maxilla in the posterior area. However, the sinus lift procedures performed in the presence of cysts, mucoceles, mucous retention cysts (MRCs), and antral pseudo-cysts could mainly decrease the sinus cavity volume and could increase the possibility of ostium obstruction and might lead to infection followed by failure of the grafting procedure. A radiological assessment should be made with computerized tomography (CT) or cone-beam CT to evaluate the remaining bone volume and to detect any pathology in the sinus. Different techniques were described in the literature for sinus lifting and bone grafting in patients with cysts. For some authors, cysts should be treated before sinus grafting and six months later, the procedure could be performed. For others, sinus lifting can be performed without lesion removal. At this time, controversy exists regarding the decision on whether lesions must be removed/aspirated or not before sinus grafting. In this study, we report a case where an MRC was aspirated and instantaneously, the sinus membrane was lifted and grafted, and implants were installed with 1-year follow-up after loading. Identifying lesions in the maxillary sinus is essential before planning any type of sinus augmentation and implant placement.